2009
DOI: 10.1071/wr08092
|View full text |Cite
|
Sign up to set email alerts
|

Assessing microhabitat use by roe deer and moose in China

Abstract: Potential conflicts between forestry production practices and wildlife habitat requirements are increasing globally with rapid socioeconomic development. Moose (Alces alces cameloides) and roe deer (Capreolus pygargus bedfordi) populations are in decline in north-eastern China, an area managed for forestry production. We obtained detailed information about these species' use of habitat by following their movement paths in snow and recording behaviours exhibited along their paths. We used fractal analysis, Mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 59 publications
(66 reference statements)
0
7
1
Order By: Relevance
“…For example, the fractal dimension is constant over a range of scales, and if there is a discontinuity in the fractal dimension, it indicates that animals' path structures change from one scale to another and that the animal responds differently to the environment. Our results showed that the fractal dimension of Amur tigers was almost constant at the fine scale range of 2-50 m, in contrast to martens (Martes americana) and ungulates (Jiang et al, 2009;Nams & Bourgeois, 2004). The range of scales at which qualitative differences in tiger pathways occur can be tested in the future.…”
Section: Quantifying Path Tortuosity Using Fractal Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…For example, the fractal dimension is constant over a range of scales, and if there is a discontinuity in the fractal dimension, it indicates that animals' path structures change from one scale to another and that the animal responds differently to the environment. Our results showed that the fractal dimension of Amur tigers was almost constant at the fine scale range of 2-50 m, in contrast to martens (Martes americana) and ungulates (Jiang et al, 2009;Nams & Bourgeois, 2004). The range of scales at which qualitative differences in tiger pathways occur can be tested in the future.…”
Section: Quantifying Path Tortuosity Using Fractal Analysismentioning
confidence: 84%
“…The divider's lower limit should not be less than the sampling accuracy (Nams & Bourgeois, 2004). According to real measurements and published references, the average step of the Amur tiger was 1.5 m (Pikunov et al, 2014), so the lower limit of the divider for the path analysis was set to 2 m, and the upper limit of the divider was decided by reviewing the literature (Jiang et al, 2009; Nams & Bourgeois, 2004); the largest divider size was selected to be 50 m.…”
Section: Methodsmentioning
confidence: 99%
“…Habitat selection is also influenced by interspecific competition (Suhling, 1996;Jiang et al, 2009;Jiang et al 2010), especially among species with similar food niche. In Taihang Mountainous regions of this study, there are sympatric species such as leopard (Panthera pardus), red fox (Vulpes vulpes), jackal (Cuon alpinus), yellow weasel (Mustela sibirica) and racoon dog (Nyctereutes…”
Section: Discussionmentioning
confidence: 99%
“…Moose also often fed higher and on larger shoots than did roe deer. By browsing patchily and focusing on exposed trees in existing gaps, moose may suppress or redistribute preferred browse, thereby modifying the environment of roe deer (Edenius et al 2002a, Jiang et al 2009). That roe deer preferred areas where moose occurred may imply a mutualistic or commensal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Our failure to discriminate characteristics of foraging sites of the 2 species at the patch scale may have been because our definition of a patch was not congruent with ungulate foraging strategies. We defined patches based on uniformity of vegetation (i.e., forest stands), but Astrom et al (1990) concluded that foraging ungulates perceive each tree as a patch, and Jiang et al (2009) found that roe deer used clusters of aspen ramets as patches (a scale almost as fine as our microhabitat scale). Moose, on the other hand, may not perceive aspen stands as discrete patches, foraging instead on aspen ramets more in accordance with diet theory than with patch use theory (Edenius et al 2002b).…”
Section: Discussionmentioning
confidence: 99%